Elemental analysis of proteins by proton induced X-ray emission (microPIXE) - Garman, E; Zeldin, O (2013)
The identification and quantification of metals bound to proteins is a crucial problem to be solved in structural biology. This chapter will describe the technique of proton induced X-ray emission with a microfocused proton beam (microPIXE) as a tool for analysing the elemental composition of liquid and crystalline protein samples. The proton beam induces characteristic X-ray emission from all elements in the protein, which can be interpreted in terms of the metal content of the protein molecule with a relative accuracy of between 10 and 20 %. The compelling advantage of this method is that the sulphur atoms in the methionines and cysteines of the protein provide an internal calibration of the number of protein molecules present so that systematic errors are minimised and the technique is entirely internally self-consistent. This is achieved by the simultaneous measurement of the energy of backscattered protons (Rutherford backscattering), to enable the matrix composition and thickness to be determined, and so correct the PIXE data for the self-absorption of X-rays in the sample. The technical and experimental procedures of the technique will be outlined, and examples of recent measurements given which have informed a range of investigations in structural biology. The use of the technique is increasing and we are in the final stages of developing it to be a routine high-throughput method. © 2013 Springer Science+Business Media Dordrecht.